(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In order to effectively organize housing reforms in the country, expand the scale of construction of New Uzbekistan housing estates and modern apartment buildings, further develop the mortgage lending market, and widely introduce into practice mechanisms for refinancing loans issued by banks using their own funds.